Pergerakan Nilai Tukar dan Pembentukan Ekspektasi Agen - Syafroni, Ayatullah; Mochtar, Karyaman (UI Scholars Hub, 2003)
It is interesting to pay attention on exchage rate phenomenon. The movement of exchange rate has free up space for the expanded model and their new variety based on theoritical and methodological issues. We apply the zone target model to explain the exchange rate movement in Indonesia during 1989-2002 in monthly basis data. We put special attention to the expectation process of the agent by confronting adaptive and rational expectation and also internalize the risk factor into the model. We found that rational expectation fit and much more be able to explain the exchange rate movement, risk averse agent and massive outflow of capital during the ciris in Indonesia. We test the robustness of our model by applying to VAR model, and the same result is conformed. This VAR specification also support the contagion effect hypothesis during the cirisis 1998.